Digital Branding and Distribution Assistance for SoE Tangerines in the Petra Farmers’ Group in South Central Timor (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
The Petra Farmers’ Group, which produces SoE Tangerines, faces challenges related to inconsistent brand identity, low adoption of digital channels, and weak distribution management, resulting in suboptimal product value and competitiveness. This initiative aims to enhance the farmers’ group’s marketing capacity through brand identity strengthening, content planning, digital channel activation, and distribution optimization. The program was implemented with 20 participants through stages of coordination, initial diagnostics, outreach, and applied training sessions lasting 60–90 minutes, as well as pre- and post-training evaluations using a 15-item questionnaire covering three indicators: brand identity and content planning, digital channels and optimization, and distribution management. The results showed a substantial increase in knowledge, with the average proportion of correct answers rising from 16.4% (pre-training) to 89.8% (post-training); the largest increase occurred in the digital channels and optimization indicator, by 81.3 percentage points. Specifically, participants produced drafts of product uniqueness narratives and seasonal content plans, activated WhatsApp Business profile and catalog features, drafted marketplace storefronts, and prepared order and shipping documentation templates. These findings indicate that practice-based digital branding training has the potential to enhance farmers’ groups’ knowledge and initial marketing readiness, although the long-term impact on actual marketing performance still requires follow-up evaluation.